2005
DOI: 10.1007/s00418-005-0088-7
|View full text |Cite
|
Sign up to set email alerts
|

Truncated HP1 lacking a functional chromodomain induces heterochromatinization upon in vivo targeting

Abstract: Packaging of the eukaryotic genome into higher order chromatin structures is tightly related to gene expression. Pericentromeric heterochromatin is typified by accumulations of heterochromatin protein 1 (HP1), methylation of histone H3 at lysine 9 (MeH3K9) and global histone deacetylation. HP1 interacts with chromatin by binding to MeH3K9 through the chromodomain (CD). HP1 dimerizes with itself and binds a variety of proteins through its chromoshadow domain. We have analyzed at the single cell level whether HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Recently, we showed that in vivo targeting of HP1␣ or HP1␤ to an amplified chromosomal region causes local chromatin condensation, enhanced trimethylated H3K9me, and recruitment of histone methyltransferases (Verschure et al, 2005). Targeting of the HP1 lacking a functional CD also caused heterochromatinization of the amplified chromosome region (Brink et al, 2006). These results show that normal binding of HP1 through its CD domain, as well as artificial binding of HP1 without a CD through lac operator-lac Repressor interaction, is sufficient to trigger heterochromatin formation.…”
Section: Discussionmentioning
confidence: 83%
“…Recently, we showed that in vivo targeting of HP1␣ or HP1␤ to an amplified chromosomal region causes local chromatin condensation, enhanced trimethylated H3K9me, and recruitment of histone methyltransferases (Verschure et al, 2005). Targeting of the HP1 lacking a functional CD also caused heterochromatinization of the amplified chromosome region (Brink et al, 2006). These results show that normal binding of HP1 through its CD domain, as well as artificial binding of HP1 without a CD through lac operator-lac Repressor interaction, is sufficient to trigger heterochromatin formation.…”
Section: Discussionmentioning
confidence: 83%
“…These results suggest that dSETDB1 is responsible for silencing the hsp26 promoter, and to a lesser extent, the hsp70 promoter. DISCUSSION Domain-dependent localization of HP1: The LacIlacO tethering system has proven useful for studies of chromosome pairing (Vazquez et al 2002), chromatin compaction (Verschure et al 2005;Brink et al 2006;Deng et al 2008;Strukov and Belmont 2009), and chromatin-mediated gene silencing (Danzer and Wallrath 2004). Previously, we demonstrated that LacI-HP1 rescues lethality in Su(var)2-5 mutants (Li et al 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Hs-alpha , HP1 Hs-beta , or a CSD to reporter genes in mammalian cell culture studies caused H3K9me3, in this case by SETDB1 (Verschure et al 2005;Brink et al 2006). Likewise, targeting HP1…”
Section: Resultsmentioning
confidence: 99%
“…11 Indeed, artificial targeting of HP1 to euchromatic sites is sufficient to induce gene repression and local condensation of chromatin in several experimental systems. [34][35][36][37] On a molecular level, HP1 might induce heterochromatin formation via cross-linking of nucleosomes in combination with the recruitment of other chromatin-modifying proteins. 38,39 The few instances where artificial HP1 targeting did not induce silencing 40 or the startling situations where HP1 has been implicated in gene activation 16,41,42 might be due to unique behavior of HP1 isoforms, distinct local chromatin environments, and the differential and regulated interaction with additional factors.…”
Section: Chromatin Histone Modifications Effector Proteins and Hetementioning
confidence: 99%